DENTAL ASPECTS OF THE SYNDROM OF INTRAUTERINE GROWTH RETARDATION IN PAST HISTORY IN PRESCHOOL CHILDREN - Garmash, О.V.; Nazaryan, R.S.; Budreiko, E.A. (World of Medicine and Biology, 2013)
The aim of the the present work was to analyze peculiarities of the oral cavity condition in preschool age patients with intrauterine growth retardation in past history. 39 patients with intrauterine growth retardation in past history were examined. The clinical, statistical methods were held. Studies have shown a high prevalence of the maxillofacial region disorders in children with the history of intrauterine growth retardation. The most considerable violations were found in patients with symmetrical form of intrauterine growth retardation.
Keywords: intrauterine growth retardation syndrome; oral cavity; primary dentition